The Implementation of QR-Code Technology on Bulak Fish Center Information System - Liantoni, Febri; Rosetya, Septiyawan; Rahmawati, Weny M. (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2018)
The technology that is currently developing is the use of QR-Code. QR-Code can convey information quickly with the acquisition of fast responses as well. QR-Code can be used on smartphones. Some media and companies widely use the QR-Code in Indonesia. QR-Code is not only used as an application identity but is also used as a means of effective, simple and modern business promotion. Making information systems for Sentra Ikan Bulak Surabaya is done by using QR-Code technology as a means of product promotion in the sales process. Research that has been done can run well and can support and be useful in improving the means of promotion. Traders find it easier to collect data on existing systems. Buyers can access the site and see reviews from other buyers so buyers will feel interested in buying the product.